1995
DOI: 10.1016/s0022-5223(95)70064-1
|View full text |Cite
|
Sign up to set email alerts
|

Combined lung and liver transplantation in patients with cystic fibrosis: A 4 1/2-year experience

Abstract: Patients with cystic fibrosis who have end-stage respiratory failure and associated liver cirrhosis have been considered poor candidates for lung transplantation because of high morbidity and mortality resulting from hepatic insufficiency after the operation. Since April 1989, our policy has been to combine heart-lung or lung and liver transplantation in this group of patients. Between June 1990 and March 1995, among 25 patients accepted in the program for combined transplantation, nine died awaiting transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 29 publications
3
64
0
1
Order By: Relevance
“…Therefore, patients with CF and end-stage complications due to liver disease (portal hypertension, variceal bleeding, ascites) and stable pulmonary function should be considered for liver transplantation. Combined lung and liver transplantation has been performed in patients with CF, but experience is limited [55]. The most appropriate intervention (repeated sclerotherapy or banding, portosystemic shunt, partial splenectomy, or liver transplantation) for the management of end-stage CF liver disease and portal hypertension is still unknown, and its identification will require larger, long-term outcome studies in subgroups of CF patients with well-defined liver disease.…”
Section: Liver Transplantationmentioning
confidence: 99%
“…Therefore, patients with CF and end-stage complications due to liver disease (portal hypertension, variceal bleeding, ascites) and stable pulmonary function should be considered for liver transplantation. Combined lung and liver transplantation has been performed in patients with CF, but experience is limited [55]. The most appropriate intervention (repeated sclerotherapy or banding, portosystemic shunt, partial splenectomy, or liver transplantation) for the management of end-stage CF liver disease and portal hypertension is still unknown, and its identification will require larger, long-term outcome studies in subgroups of CF patients with well-defined liver disease.…”
Section: Liver Transplantationmentioning
confidence: 99%
“…Whilst the combination of end-stage lung and liver disease in these patients is particularly challenging both surgically and in their post-operative management the outcome is surprisingly optimistic. One study has shown an actuarial survival of 70% at 3 years which is as good if not better than other reports of isolated lung transplantation [46]. The genetic nature of the condition is such that recurrence in transplanted organs is highly unlikely and this has been demonstrated for lung transplantation and liver transplantation.…”
Section: Lung and Lung Liver Transplantationmentioning
confidence: 89%
“…Transplantation of the heart with discontinuation of cardio-pulmonary bypass, leaving the chest opened. The liver transplantation was performed as a second step through a bilateral sub-costal incision with extension in the midline to the sternotomy (Couetil et al, 1995) and was accomplished by a caval sparing hepatectomy with an anastomosis between the donor supra-hepatic cava and the recipient left/middle hepatic vein trunk. Biliary tubes were inserted through the donor cystic duct stumps whenever possible, and the abdomen was closed over drains after achieving hemostasis.…”
Section: Surgical Approaches For Chltxmentioning
confidence: 99%